Looking into the faintEst WIth MUSE (LEWIS): Exploring the nature of ultra-diffuse galaxies in the Hydra I cluster III. Untangling UDG 32 from the stripped filaments of NGC 3314A with multi-wavelength data - Hartke, Johanna; Iodice, Enrichetta; Gullieuszik, Marco; Mirabile, Marco; Buttitta, Chiara; Doll, Goran; D'Ago, Giuseppe; de la Casa, Clara C.; Hess, Kelley M.; Kotulla, Ralf; Poggianti, Bianca; Arnaboldi, Magda; et al. (EDP SCIENCES S A, 2025)
Context. UDG 32 is an ultra-diffuse galaxy (UDG) candidate in the Hydra I cluster that was discovered in the extended network of stellar filaments of the jellyfish galaxy NGC 3314A. This jellyfish galaxy is affected by ram pressure stripping and it is hypothesised that UDG 32 may have formed from this stripped material.
Aims. The aim of this paper is to address whether UDG 32 can be associated with the stripped material of NGC 3314A and to constrain its formation scenario in relation to its environment.
Methods. We use new integral-field spectroscopic data from the MUSE large programme 'LEWIS' in conjunction with deep multi-band photometry to constrain the kinematics of UDG 32 via spectral fitting and its stellar population properties with spectral energy distribution fitting.
Results. The new MUSE data allow us to reveal that the stripped material from NGC 3314A, traced by emission lines such as H alpha, extends much further from its parent galaxy than previously known, completely overlapping with UDG 32 in projection, and with ram pressure induced star formation. We determine the line-of-sight velocity of UDG 32 to be v(LOS) = 3080 +/- 120 km s(-1) and confirm that UDG 32 is part of the same kinematic structure as NGC 3314A, the Hydra I cluster south-east subgroup. By fitting the UV and optical spectral energy distribution obtained from deep multi-band photometry, we constrain the stellar population properties of UDG 32. We determine its mass-weighted age to be 7.7(-2.8)(+2.9) Gyr and its metallicity to be [M/H] = 0.07(-0.32)(+0.19) dex. We confirm the presence of two globular clusters (GCs) in the MUSE field of view, bound to the Hydra I cluster rather than to UDG 32, making them part of the Hydra I intracluster GC population.
Conclusions. The metal-rich and intermediate-age nature of UDG 32 points towards its formation from pre-enriched material in the south-east group of the Hydra I cluster that was liberated from a more massive galaxy via tidal or ram-pressure stripping, but we cannot establish a direct link to the ram-pressure stripped material from NGC 3314A.